Recognition in interaction: theoretical and empirical observations - Koskinen, Emmi; Laitinen, Arto; Stevanovic, Melisa (Frontiers in Sociology, 2024)
In the current paper we aim to combine the theoretical ideas of recognition theory to conversation analytical, empirical observations. We ask what recognition theories can give to conversation analysis, and vice versa. We operate on a model of recognition that consists of three different modes: respect, esteem, and love/care, and which distinguishes the levels of conversational actions and the attitudes of recognition manifested in such actions. In this study we examine data examples from various conversational settings (institutional, quasi-experimental, family interaction) and activities (decision-making, storytelling), focusing on the more complex cases of (mis)recognition. We show how recognition can appear both explicitly and implicitly in conversational sequences, and demonstrate how the levels of conversational actions and recognition can be either congruent or incongruent with each other. At the end of the article, we discuss the implications of this view for the interface of conversation analysis and sociological theory, arguing that it can inform and promote the development of interactionally based social and societal critique.